Generating game immersion features for immersive game selection - Umar, Najirah; Yuyun, Yuyun; Gani, Hamdan (Prodi Teknik Informatika FIK Universitas Muslim Indonesia, 2022)
The immersion is an essential component of the modern digital game. Currently, immersion is the required component which should be included in the digital game. The modern game which success within game industry surely has included immersion as a component. Although digital games have been introduced for many years, yet what is immersion game been known very little. Regarding the intensive study about user immersion, there is still a lack of knowledge about game immersion. First, the game designers, game developers, and gamers are facing problems how to understand whether their game is immersive or not. There is no knowledge regarding how to evaluate their game, whether immersive or not, and this process requires expert knowledge. Second, currently, the game designers are relied on speculative interpretation to evaluate their game because there is no method to examine whether the game is immersive or not. Therefore, this study aims to propose a method that enable to evaluate if the game is immersive or not. This method is emerged as knowledge and recommendation that quickly be able to assist the game designers, game developers, and gamers evaluating whether a game is immersive or not. First, this research conducts a literature review to categorize the game immersion features. Second, this study proposes an effective method that can analyse and recommends whether a game is immersive or not. Finally, this study reveals that the finding could be used as a recommendation for the other immersive technology platforms.